THE CONCEPT OF LOVE FOR HUMANITY AND HUMANISM IN THE EPIC OF MANAS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
One of the deeply philosophical meanings of the epic of Manas is the idea of mercy and love for humanity. This idea, which forms the spiritual foundation of the work, is revealed through Manas’s justice, generosity, and humanism, demonstrated not only toward his own people but also toward other nations. The purpose of this article is to demonstrate that the spirit of love for humanity in Manas is not simply a personal quality of the hero, but an artistic reflection of the cultural values and spiritual worldview of the Kyrgyz people. Furthermore, the paper examines the significance of these values for strengthening national unity and the harmonious development of modern society.